Studying the structure and some properties of R.F. magnetron sputtered ZnO:Al films - Ngo, Huong Thu; Ta, Canh Dinh; Nguyen, Phuong Duy; Nguyen, Long Ngoc (VNU Journal of Science: Mathematics - Physics; Vol 20 No 3AP, 2017)
Abstracts